Effect of lithium carbonate on nickel catalysts for direct internal reforming MCFC - Choi, JS; Yun, JS; Kwon, HH; Lim, TH; Hong, SA; Lee, HI (ELSEVIER SCIENCE BV, 2005)
Despite many advantages of the direct internal reforming molten carbonate fuel cell (DIR-MCFC) in producing electricity, there are many problems to solve before practical use. The deactivation of reforming catalyst by alkali like lithium is one of the major obstacles to overcome. A promising method is addition of TiO2 into the Ni/MgO reforming catalyst, which resulted in the increased resistance to lithium poisoning as we previously reported. To understand how added titania worked, it is necessary to elucidate the deactivation mechanism of the catalysts supported on metal oxides such as MgO and MgO-TiO2 composite oxide. Several supported nickel catalysts deactivated by lithium carbonate were prepared, characterized and evaluated. The Ni/MgO catalyst turned out to be most vulnerable to lithium deactivation among the employed catalysts. The activity of the Ni/MgO gradually decreased to zero with increasing amount of lithium addition. Deactivation by lithium addition resulted from the decrease of active site due to sintering of nickel particles as well as the formation of the LiyNixMg1-x-yO ternary solid solution. These were evidenced by H-2 chemisorption, temperature programmed reduction, and XRD analyses. As an effort to minimize Li-poisoning, titanium was introduced to MgO support. This resulted in the formation of Ni/Mg2TiO4, which seemed to increase resistance against Li-poisoning. (c) 2005 Elsevier B.V. All rights reserved.
Keywords: DOPED NI/MGO CATALYSTS; MECHANISM; METHANE; SYSTEM; VAPOR; PHASE; OXIDE; SIZE